ALGORITMA GENERATE AND TEST UNTUK OPTIMALISASI MASALAH RUTE PERJALANAN - Khairunnisak Khairunnisak; Dina Fajar Sulistiyani; Zezya Ramadhany (LPPM STMIK STIKOM Indonesia, 2021)
The common of urban city problem is a traffic jam, and it is heavily affect the public transportation service quality. Many cities in tropical countries suffer of heavy traffic jam due to the populaition of motorbike. According to Central Java Province Government, in 2014 the population of motorcycle is 439.418 units with the ownership ratio at 0.75 unit/person. Solo is one of typical middle size city in Central Java, Indonesia. Solo suffers from traffic jam in particular time of the day and it affect the quality of service of batik solo as the mass transportation service in Surakarta. This research would like to help the community get the optimal travel route with the fastest time, especially at the busiest times. The method used is Generate and Test algorithm. This method is a combination of Depth First Search and Backtracking. This research is conducted to get information about the influence of traffic volume, service road level and traffic jam level toward the time needed for Batik Solo Trans to find the optimal route. There is a route that been selected to be the most optimal route by considering the factors that influence it and the algorithm applied